CUSTOMER RELATIONSHIP MANAGEMENT DALAM MEMBENTUK KEPUASAN PELANGGAN DAN LOYALITAS PELANGGAN - Vetty Widya Setyaningrum, Marjam Desma Rahadhini & Sunarso (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2018)
Cafe is an exciting place to hangout with friends. Some cafes around uns are quite famous among the public. The purpose of this research is to analyze the level of customer satisfaction and customer loyalty by using crm (commitment, communication, and service quality). The research uses quantitative data type and data collection techniques in this study using primary data with convenience sampling method with the number of respondents as many as 140 people. Validity and reliability testing using confirmatory factor analysis and cronbach’s alpha and analysis method used is Structural Equation Modeling. The result of this study indicate that there is a significant effect on CRM to customer satisfaction, CRM to customer loyalty, and CRM to customer loyalty through customer satisfaction.Keywords: CRM (commitment, communication, and service quality), customer satisfaction, customer loyalty.